Level of Teacher’s Preparedness in Teaching towards Disabled Student in Vocational Special Education School/ Tahap Kesediaan Guru Mengajar Pelajar Kurang Upaya (OKU) di Sekolah Menengah Pendidikan Khas Vokasional (SMPKV) (Sains Humanika, 2020)
The research on teacher readiness in teaching students with disabled is beneficial to teachers especially who are not exposed to the basics of Special Education knowledge. This research was conducted to identify the level of readiness of teachers from pedagogical aspect and communicating with disabled students during the learning and facilities process. The research was conducted at two Malaysian Vocational Special Education Secondary Schools. The total number of respondents involved in this research was 76 teachers. Quantitative methods are used by researchers in conducting research. Statistical Packages for Social Science Version 25.0 (SPSS 25.0) was used to analyze data for questionnaire instruments. The reliability of the questionnaire through a pilot study was 0.984 for the pedagogical aspect and 0.858 for the communication aspect. The findings show that the item has a positive and readiness in communicating. Therefore, in conclusion, the findings of this study are shown the level of teacher readiness for disabled students is high and ready.
Keywords: Special education; pedagogy; communication; teacher; disabled student